2017
DOI: 10.1016/j.chembiol.2017.02.011
|View full text |Cite
|
Sign up to set email alerts
|

FRET-Based Sensors Unravel Activation and Allosteric Modulation of the GABAB Receptor

Abstract: The main inhibitory neurotransmitter, γ-aminobutyric acid (GABA), modulates many synapses by activating the G protein-coupled receptor GABA, which is a target for various therapeutic applications. It is an obligatory heterodimer made of GB1 and GB2 that can be regulated by positive allosteric modulators (PAMs). The molecular mechanism of activation of the GABA receptor remains poorly understood. Here, we have developed FRET-based conformational GABA sensors compatible with high-throughput screening. We identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 59 publications
5
41
1
Order By: Relevance
“…Our hypothesis is supported by our experiments, in which decreasing the conformational heterogeneity using a set of mutations aimed at stabilizing the receptor in its inactive conformation led to an increase in mGlu 2 oligomerization. Of interest, the VFT dimer of the GABA B receptor has been proposed to undergo smaller conformational changes compared to mGlu receptors 49 , 50 . This potentially smaller conformational heterogeneity could explain why the GABA B receptor can form larger oligomers without ligand at low receptor density 12 , 15 , 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Our hypothesis is supported by our experiments, in which decreasing the conformational heterogeneity using a set of mutations aimed at stabilizing the receptor in its inactive conformation led to an increase in mGlu 2 oligomerization. Of interest, the VFT dimer of the GABA B receptor has been proposed to undergo smaller conformational changes compared to mGlu receptors 49 , 50 . This potentially smaller conformational heterogeneity could explain why the GABA B receptor can form larger oligomers without ligand at low receptor density 12 , 15 , 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Single-molecule Förster resonance energy transfer (smFRET) studies of mGluRs showed that the VFTs oscillate between the open/inactive and closed/active conformation and that binding of an agonist shifts the conformational equilibrium towards the closed state [41,42]. This mechanism has not been confirmed for the GABAB-R, and conformational rearrangements associated with activation of the GABAB-R are found to be smaller than what is observed for mGluRs [6,36,43,44]. The open/inactive and closed/active states of GABAB-R are likely to be the main conformational states of Sequence analysis showed that none of the residues associated with ligand binding in the GABA B1b VFT are conserved in the GABA B2 VFT [37], and the sequence homology between the VFTs is 33% [22].…”
Section: The Extracellular Domainsmentioning
confidence: 92%
“…PAMs potentiate the receptor activation induced by an orthosteric agonist, and some PAMs also display intrinsic agonist activity and are named ago-PAMs [55]. FRET studies have also shown that ago-PAMs can actually cause movements of the GABA B1 VFT and the 7TM, corresponding to the conformational changes observed upon agonist activation [43]. NAMs inhibit or reduce responses produced by orthosteric agonist, either by stabilizing an inactive conformation of the 7TM domain, and/or decrease the agonist affinity.…”
Section: Allosteric Binding Sitementioning
confidence: 99%
“…The different leaving groups for BMTP versus BETP (methyl versus ethyl sulfenate) are potential candidates, as sulfenic acids are known signaling intermediaries in the context of cysteine modification . In addition, further studies using recently described conformational FRET sensors, or concentration responses to calculate alpha values, are required to unambiguously demonstrate the differential actions of the prearranged PAMs at the GLP‐1R. It should be noted that the herein‐described prearranged PAMs, as well as BETP , exist as racemates, and in the future it will be interesting to study the labeling kinetics of the separate enantiomers before chirality is lost through covalent modification of GLP‐1R.…”
Section: Figurementioning
confidence: 99%